Using simulation in a vocational programme : Does the method support the theory? - Rush, Sue [Verfasser]; Acton, Lesley [Verfasser]; Tolley, Kim [Verfasser]; Marks-Maran, Di [Verfasser]; Burke, Linda [Verfasser] (My University, 2010)
"Use of simulation is well established as a way of learning and assessing skills in vocational disciplines. In many institutions the use of simulation with student nurses is being tested as a way of helping them learn clinical skills, problem-solving, clinical assessment and decision-making. This paper explores the value of simulation as a learning tool through the presentation of findings from an evaluative research project into the use of simulation in nursing education. The focus of this paper is how students perceive that simulations help them learn and suggests that simulation may play a part in how students perceive learning that is meaningful to them. A literature review on the use of simulation is presented together with literature related to the learning theory that underpins simulation. The methodology, data collection and findings of the evaluative study are then presented followed by a discussion of the findings. Although the original research did not set out to examine how students perceived that simulations influenced their learning, the analysis indicated that this was a significant issue for them. Conclusions are drawn about how learning theory and simulation can be brought together to enhance student learning." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 3 Lehr-Lern-Forschung; S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; I 2.2.1 Westeuropa; Berufsausbildung; Lerntheorie; Simulation; Gesundheitsberuf; Großbritannien